Reasons for reducing radiation at Semipalatinsk Nuclear test site (Journal of Geography and Environmental Management, 2016)
This article describes the reasons for reduction of radiation at Semipalatinsk nuclear test site: first period half-life of a radioactive isotope. Currently, the level of radiation at the Semipalatinsk nuclear test site composes from 6 to 20 micro-roentgen per hour. Only at some points the radiation level higher than the plains. In this regard, our aim is to clarify the cause of the reduction of radiation and space distribution of nuclear residues at Semipalatinsk nuclear test site. Second is radionuclide flushing with water, soaking with soil, picking up ground water. Counting the number of flushing water depends rainfall in the warm season. Third is influence of organisms in order to reduce radiation. The plants and animals actively participate to reduce radiation. The plant gives a lot of biological products. The study used methods: general scientific, cartographic method, comparative, quantitative mass spectrometry.
Keywords: nuclear test; radionuclide; Semipalatinsk; radioactive isotope